2023
DOI: 10.1021/acs.energyfuels.3c01950
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Green Ammonia for Resilient and Cost-Competitive Islanded Electricity Generation from Hybrid Solar Photovoltaic–Wind Farms: A Case Study in South Africa

Victor N. Sagel,
Kevin H. R. Rouwenhorst,
Jimmy A. Faria

Abstract: Hybrid solar photovoltaic (PV) and wind generation in combination with green ammonia as a seasonal energy storage vector offers an excellent opportunity to decrease the levelized cost of electricity (LCOE). In this work, an analysis is performed to find the most cost-effective configuration of powerto-ammonia-to-power (P2A2P). In P2A2P, wind and solar resources are combined with energy storage to design a resilient electricity grid. For daily generation, batteries are utilized for energy storage, whereas ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A trade-off between kinetics and equilibrium is accomplished through the use of temperatures between 320 and 550 • C and pressures between 150 and 300 bars [44]. Sagel et al [45] indicate that for a relatively small-scale process, it is beneficial to work at moderate process conditions: 350-525 • C and 100-200 bar. Employing multiple catalyst beds arranged in series along with an intercooler system is a method that is utilized in the chemical industry to reconcile the trade-off between thermodynamics and kinetics.…”
Section: Haber-bosch Process For the Synthesis Of Ammoniamentioning
confidence: 99%
See 2 more Smart Citations
“…A trade-off between kinetics and equilibrium is accomplished through the use of temperatures between 320 and 550 • C and pressures between 150 and 300 bars [44]. Sagel et al [45] indicate that for a relatively small-scale process, it is beneficial to work at moderate process conditions: 350-525 • C and 100-200 bar. Employing multiple catalyst beds arranged in series along with an intercooler system is a method that is utilized in the chemical industry to reconcile the trade-off between thermodynamics and kinetics.…”
Section: Haber-bosch Process For the Synthesis Of Ammoniamentioning
confidence: 99%
“…Sagel et al [45] indicated that moderate temperatures and pressures are preferred for small-scale ammonia production plants. Spatolisano et al [24] indicated that when applied to small-scale production plants, NH 3 synthesis has to be performed at lower pressures in order to reduce operating costs, but low pressures negatively affect the chemical equilibrium of the reacting system; consequently, the authors used 200 bar.…”
Section: Influence Of Pressure On Ammonia Conversionmentioning
confidence: 99%
See 1 more Smart Citation